Numerical study of horizontal hydraulic fracture propagation in multi-thin layered reservoirs stimulated by separate layer fracturing. Issue 1 (2nd January 2020) - Gao, Qi; Cheng, Yuanfang; Yan, Chuanliang
ABSTRACT: Separate layer fracturing (SLF) technique is the prevailing method for stimulating multi-thin layered reservoirs (MTLRs) whereas the production record reveals that not all wells show good performance after being fractured. The primary cause for this phenomenon can be attributed to the complex geometry of the created hydraulic fractures. For better understanding the problem, we establish a new geomachanical model based on the extended finite element method (XFEM) and cohesive zone method (CZM), to investigate the fracture propagation in MTLRs under SLF. Reverse faulting stress regime is considered. In the simulation procedure, horizontal hydraulic fractures (HHFs) are created sequentially from the bottom up along a vertical wellbore. The results show that later created HHFs will propagate out of the pay zones or probably enter the water or gas-bearing layers if the fracturing time is not reasonably controlled. The fracture initiation pressure (FIP) and fracture propagation pressure (FPP) present larger values when stimulating the upper formations, and the deviation of later created HHFs can lead to the building up of FPP. Parametric studies indicate that larger injection rate and shallower reservoir depth yields longer and wider HHFs while smaller injection rate, shallower reservoir depth and thicker barriers results in lower FIP and FPP.